HEART RATE, MOOD STATES, AND RATING OF PERCEIVED EXERTION AMONG ELDERLY SUBJECTS DURING 3.5 HOURS OF RECREATIONAL ALPINE SKIING - Sabine Krautgasser; Peter Scheiber; Serge P. von Duvillard; Erich Müller (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2012)
A decline in physiological functioning and mental wellbeing is common with advancing age. However, these changes may vary among elderly individuals. Physical activity and the response of the elderly to exercise during recreational activities, i.e., recreational alpine skiing, may serve as a catalyst for the improvement of wellbeing and general health. Purpose: The aim of the study was to assess the heart rate (HR) response modulations in a group of elderly recreational alpine skiers during 3.5h of skiing. In addition, each group's perceived responses of mood state (MS) and rating of perceived exertion (RPE) were collected to determine possible contributions to changes in wellbeing as a result of recreational skiing. Methods: Forty-nine healthy elderly participants (mean age: 63±6 yrs, weight: 75.4+13.1 kg, height: 170.5+9.1 cm, BMI: 26+3.2) with at least basic alpine skiing ability participated in a 3.5h ski test. GPS data (GPS Garmin Forerunner 301) were used to monitor altitude and HR and were recorded continuously during the 3.5h of skiing. During skiing, participants were asked at three different times to report RPE and MS. Results: The time spent on the lift during the 3.5h skiing ranged from 21-58% followed by recovery breaks of 17-53% and time spent in downhill skiing ranged from 12-40%. Participants completed 9-23 downhill runs in 3.5h. Average intensities during 3.5 h downhill runs for over 80% of the group were between 50-80% of maximal heart rate (HRmax) (220-age). Peak heart rate (HRpeak) values during downhill runs for 35% of the group were between 60-70% of HRmax. Statistical analysis revealed numerous significant differences between RPE and MS values for the three different sampling times. The MS in general remained positive and even increased in the categories of happiness and sociability despite an increase in fatigue. Conclusion: The results of this study suggest that the duration and intensity of skiing was appropriate and yielded immediate positive psychological effects on the elderly subjects. Furthermore, recreational alpine skiing has a positive effect on MS ratings reflecting wellbeing, while generating age-appropriate moderate RPE values in elderly alpine skiers.